Penetapan Kadar Tanin Dari Bunga Telang (Clitoria ternatea L.) Secara Permanganometri - Choiril Hana Mustofa; Anita Agustina Styawan; Nofia Putri Lestari (STIKES MUHAMMADIYAH KLATEN, 2021)
Telang flowers can be found thriving in watery areas in Indonesia, their purple flowers bloom throughout the year. Telang flowers have been studied to contain phenolic chemicals, flavonoids, anthocyanins, flavonol glycosides, kaempferol glycosides, quercetin glycosides, myristetin glycosides, terpenoids, flavonoids, tannins and steroids. Tannins are plant polyphenols that function to bind and precipitate proteins. In the world of tannin medicine serves to treat diarrhea, stop bleeding, and treat hemorrhoids. There are two main types of tannins namely condensed tannins and hydrolyzed tannins. The purpose of this study was to determine the tannin content in the extract of telang (Clitoria ternatea L.) flowers using the permanganometric method. Determination of tannin levels by permanganometric method. Permanganometry is a titration method using potassium permanganate, which is a strong oxidizing agent as a titrant. This property of KMnO4 is known as an auto-indicator. The result of the determination of the tannin content of the telang flower (Clitoria ternatea L.) by permanganometry was 13.86% b/b.